Structural colors: from natural to artificial systems. (8th March 2016) - Fu, Yulan; Tippets, Cary A.; Donev, Eugenii U.; Lopez, Rene
Abstract : Structural coloration has attracted great interest from scientists and engineers in recent years, owing to fascination with various brilliant examples displayed in nature as well as to promising applications of bio‐inspired functional photonic structures and materials. Much research has been done to reveal and emulate the physical mechanisms that underlie the structural colors found in nature. In this article, we review the fundamental physics of many natural structural colors displayed by living organisms as well as their bio‐inspired artificial counterparts, with emphasis on their connections, tunability strategies, and proposed applications, which aim to maximize the technological benefits one could derive from these photonic nanostructures. WIREs Nanomed Nanobiotechnol 2016, 8:758–775. doi: 10.1002/wnan.1396 This article is categorized under: Diagnostic Tools > Biosensing Diagnostic Tools > In Vitro Nanoparticle-Based Sensing Nanotechnology Approaches to Biology > Nanoscale Systems in Biology